Revealing of Macroinvertebrate Communities as Ecological Integrity of Water Quality: A Case Study in Kali Lamong Estuary - Kevin Daffa Prasetya; Achmad Chusnun Ni'am (School of Postgraduate Studies, Diponegoro Univer, 2025)
Every country has water pollution and there are various ways to assess it, including physicochemical and biological parameters. This study examined river water quality utilizing macroinvertebrates as pollution indicators. Biological Monitoring Working Party Average Score Per Taxon is calculated. Sediment sampling was conducted using a Van Veen Grab sampler to evaluate water quality using biological indicators. Furthermore, physicochemical parameter has been conducted in the same sites with the sediment samples site for determining water quality associated with macroinvertebrates. This study contains 3 stations A, B, and C with 3 sampling points. The area had 3 taxas of 8 macroinvertebrate families: Pachychidae, Viviparidae, Sphaeriidae, Piscicolidae, Neritidae, Chironomidae, Planorbidae, and Mollanidae. Due to the study's location in the river estuary, where pachychidae reside on the coast, they are the most common macroinvertebrates. Viviparidae inhabit waters of rivers. Water contamination scores are calculated using the Biological Monitoring Working Party Average Score Per Taxon (BMWP-ASPT) score. BMWP-ASPT scores from all stations range from 3.67 to 5.33, macroinvertebrate analysis with BMWP-ASPT method points A1, A2, A3, B1, B2, B3, and C1 include moderately and heavily polluted, and almost all physicochemical parameters have a correlation with BMWP-ASPT, except for PO4, which does not meet the statistical analysis limit.